The redistribution of trade gains when income inequality matters - Marco De Pinto (Economies, 2015)
How does a redistribution of trade gains affect welfare when income inequality matters? To answer this question, we extend the [1] model to unionized labor markets and heterogeneous workers. As redistribution schemes, we consider unemployment benefits that are financed either by a wage tax, a payroll tax or a profit tax. Assuming that welfare declines in income inequality, we find that welfare increases up to a maximum in the case of wage tax funding, while welfare declines weakly (sharply) if a profit tax (payroll tax) is implemented. These effects are caused by the wage tax neutrality (due to union wage setting) and by a profit tax-induced decline in long-term unemployment. As a result, the government's optimal redistribution scheme is to finance unemployment benefits by a wage tax.
Keywords: F1; F16; H2; 330; trade liberalization; redistribution; income inequality; heterogeneity; trade unions